Skriftuurlike perspektiewe op die effek van doop op vergifnis - Barend J. de Klerk (Verbum et Ecclesia, 2013)
Scriptural perspectives on the effect of baptism on forgiveness. This article focused from a Scriptural perspective on the question of whether baptism can and should have an effect on forgiveness and reconciliation in the South African society. This aspect was examined because in one of the most widely used confessionals of the worldwide church, the Nicene Creed, the following words are found: We believe in one baptism for the forgiveness of sin. Another reason for investigating the effect that baptism should have on forgiveness and reconciliation is the connection between Gods forgiveness and the calling on the baptised to forgive. The article highlighted the following five key points: God acts in baptism; the Triune God works in baptism; the covenant relationship is expressed in baptism; baptism is a baptism in Christs death and resurrection; Gods forgiveness and reconciliation in baptism call the baptised to forgive.